Correlation between Psychomotor Skills and Some Academic Scores of Dental Students: A Longitudinal Study - Hamid Reza Poreslami; Hoda Shamsadini; Hamid Sharifi; Simin Ghanbari Gohari (Kerman University of Medical Sciences, 2015)
Background & Objective: The profession of dentistry necessitates the proficiency of students not only in theoretical knowledge but also in psychomotor skills Many dentistry skills in addition to theoretical courses are taught through practical courses The aim of the present research was to investigate the correlation between psychomotor skills and academic scores from theoretical and practical courses among a group of dental students   Methods: In this study the psychomotor skills of 33 dental students in their first term in 2010 and before taking any practical courses were evaluated through a practical test After being presented with an image the students were asked to build a sample of that image with a certain type of dough in a determined duration of time and simultaneously Each students work was evaluated separately by professors of the Department of Pediatric Dentistry The mean of the scores given by 6 professors was considered as the psychomotor skill score of the participants After 3 years the scores were compared with those obtained by the same students from theoretical and practical lessons of Endodontics 1 and Restorative Dentistry 1 The partial correlation coefficient was used to determine the correlation between the scores   Results: There was a significant correlation between the practical test score and the practical Endodontics (r = 051 P = 0020) and Restorative Dentistry (r = 035 P = 0040) scores However no significant correlation was observed between practical test scores and theoretical Endodontics and Restorative Dentistry scores   Conclusion: There is a significant correlation between dental students psychomotor skills and the scores of their practical courses Practical examination at the time of the students entrance into the university or enhancement of their psychomotor skills may improve their work